Modulatory Effects of Plant Polyphenols on Bone Remodeling: A Prospective View From the Bench to Bedside - Nicolin, Vanessa; De Tommasi, Nunziatina; Nori, Stefania Lucia; Costantinides, Fulvia; Berton, Federico; Di Lenarda, Roberto (Frontiers in Endocrinology, 2019)
During the past, a more comprehensive knowledge of mechanisms implicated in bone resorption processes has driven researchers to develop a compound library of many small molecules that specifically interfere with the genesis of osteoclast precursors cells. Natural compounds that suppress osteoclast commitment may have therapeutic value in treating pathologies associated with bone resorption like osteoporosis, rheumatoid arthritis, bone metastasis and periodontal disease. The present review is focused on the current knowledge on the polyphenols derived from plants that could be efficacious in suppressing osteoclast differentiation and bone resorption.